Analisis Hukum Terhadap Kurangnya Transparansi Serta Akuntabilitas Pelaporan Keuangan Dalam Suatu Perusahaan - Az’zahra, Maura Hanisa; Wahyuningsih, Theresia Lintang; Atriani, Dewi; Savitri, Pitaloka Alif; Stefano, Jeremia Lorenzo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Legal analysis of corporate financial transparency and accountability is an important study in the context of corporate governance and financial market integrity. In an information-driven environment, transparency in financial reporting is key to ensuring stakeholder trust and market efficiency. However, the lack of transparency and accountability in financial reporting is often a disturbing issue, raising questions about the legal framework that regulates it and the legal implications of these practices. A lack of transparency in financial reporting not only creates risks for stakeholders, such as investors and creditors, but can also disrupt market efficiency by increasing asymmetric information. Therefore, law enforcement against financial reporting violations is important in ensuring company compliance with applicable transparency standards.